2009
DOI: 10.1590/s0100-204x2009000700015
|View full text |Cite
|
Sign up to set email alerts
|

Dieta com alto teor de gordura e desempenho de tourinhos de grupos genéticos diferentes em confinamento

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desempenho em confi namento de tourinhos de quatro grupos genéticos distintos tratados com dietas com diferentes teores de gordura. Foram utilizados nove animais Nelore, nove Caracu, dez ½ Caracu ¼ Angus ¼ Nelore e dez ½ Red Angus ¼ Caracu ¼ Nelore, com massa corporal inicial de 227±33 kg e dez meses de idade, distribuídos aleatoriamente em dois tratamentos nutricionais: baixo teor de gordura (3,15% de extrato etéreo) e alto teor de gordura (7,28% de extrato etér… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
7
1
3
Order By: Relevance
“…Therefore, carcass must provide maximum amount of muscle, minimum of bone, and an amount of fat that varies depending on consumer preference. The proximate composition of the beef was similar between treatments and with values similar to those obtained by Lawler et al (2004), Freitas et al (2008), Razook et al (2002), Rubiano et al (2009), Souza et al (2009), and Sestari et al (2012, when working with Nelore cattle. The exception is ether extract content, which was lower, possibly due to the lower energy density of the diets used in this study compared with the aforementioned authors, who aimed at higher weight gain.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Therefore, carcass must provide maximum amount of muscle, minimum of bone, and an amount of fat that varies depending on consumer preference. The proximate composition of the beef was similar between treatments and with values similar to those obtained by Lawler et al (2004), Freitas et al (2008), Razook et al (2002), Rubiano et al (2009), Souza et al (2009), and Sestari et al (2012, when working with Nelore cattle. The exception is ether extract content, which was lower, possibly due to the lower energy density of the diets used in this study compared with the aforementioned authors, who aimed at higher weight gain.…”
Section: Discussionsupporting
confidence: 78%
“…These tissue proportions can be explained by the grazing system and were similar to those reported by several authors working with Nelore and their crossbreds fed Brachiaria sp., with or without supplementation of corn and wheat bran (Razook et al, 2002;Vaz et al, 2002;Ribeiro et al, 2004;Freitas et al, 2008;Souza et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…A massa de forragem disponível durante todo o período experimental sempre foi superior a 4.823kg de MS/ha, ou seja, maior que os 2.000kg de MS/ha, considerados por Minson (1990) A literatura demonstrou efeito do grão de soja "in natura" ou tostado na redução do consumo de MS (4 a 27%) em experimentos com diferentes inclusões do grão (13 a 27% na MS) tanto na dieta de bovinos como de outras espécies (Vargas et al, 2002;Jordan et al, 2006;Oliveira et al, 2007;Silva et al, 2007;Souza et al, 2009 Concentrados: T0; T1,3; T2,6 e T3,9 -suplementos concentrados sem inclusão de grão de soja tostado (GST) e com inclusão de 1,3; 2,6 e 3,9kg de GST (base matéria natural); EPM = Erro-padrão da média ; ns = não-significativo (P>0,05); AG = ácidos graxos.…”
Section: Resultsunclassified
“…In addition, animals from industrial cross-breeding (½ Angus) are slaughtered one generation before those which come from absorbent crossbreeding (¾ Angus), thus increasing the turnover of animals in the production system, reflecting in a greater number of animals slaughtered for a particular period of time. Some authors have observed different results, in which pure Nelore cattle presented lower weights at slaughter in extra-young systems when compared to European breeds (PEREIRA et al, 2009;RUBIANO et al, 2009;SOUZA et al, 2009). This is possibly due to differences in the environmental conditions in which the experiments were conducted.…”
Section: Resultsmentioning
confidence: 99%